PATIENT EMPOWERMENT INDEX OF DIABETES MELLITUS PATIENTS - Darjono, Agus Heru; Sumarwan, Ujang; Yuliati, Lilik Noor; Wijayanto, Hari (Jurnal Ilmu Keluarga dan Konsumen, 2019)
The measurement of patient empowerment is important in the health care of chronic diseases, especially diabetes mellitus. The purpose of the study was to develop the patient empowerment index (‘IKP’/Indeks Keberdayaan Pasien) and its dimensions (patient knowledge, patient control, and patient participation) in patients with diabetes mellitus. The research utilized factor analysis in developing patient empowerment index for data analysis. Purposive sampling has been conductedwith 330respondents of diabetes mellitus patients from 26 hospitals in Jabotabek (Jakarta, Bogor, Tangerang, and Bekasi). The variables measured using the Likert scale with a scale of 1 to 5, in which 1 indicates the level of strongly disagree and 5 indicates the level of strongly agree. The collected data were analysed with factor analysis.The results showed that the patient empowerment index consisted of 25.84 percent of knowledge dimensions, 33.44 percent of control dimensions and40.76 percent of participation dimensions. The total score of patient empowerment index value is 68.84 that is in the critical category, which means that consumers have control for the management of their disease conditions in their daily lives. The managerial implication based on the result was the emerging issues of the government to develop an empowerment index for each province in Indonesia that can be used as a benchmark and key performance indicator (KPI) to measure the governance of health programs so the patient empowerment can be increased.